Regular-uniform convergence and the open-open topology - Kathryn F. Porter (International Journal of Mathematics and Mathematical Sciences)
In 1994, Bânzaru introduced the concept of regular-uniform, or r-uniform, convergence on a family of functions. We discuss the relationship between this topology and the open-open topology, which was described in 1993 by Porter, on various collections of functions.